Combination of active and inactive yeast and its use as an additive for confined ewe lambs: nutritional parameters - Miranda Feitosa, Tays Raniellen; Sousa, Luciano Fernandes; Ferreira, Deborah Alves; Oliveira, Karla Alves; Schultz, Erica Beatriz; de Oliveira, Marcela Rodrigues; Santos Siqueira, Marco Túlio [UNESP]; Gonçalves Vilaça, Lucas Eduardo; de Sousa, Jhone Tallison Lira; Macedo Junior, Gilberto de Lima (Universidade Estadual de Londrina, 2025)
This study aimed to evaluate the effects of adding increasing levels of a combination of active and inactive yeast (Milk Sacc X® - Alltech®, Maringá, Paraná, Brazil, 5.0 x 108 CFU) on the consumption and apparent digestibility of dry matter (DM) and its components, as well as the nitrogen and energy balances of lambs fed high-concentrate diets. Five Dorper x Santa Inês crossbred lambs, averaging an initial weight of 40.40 ± 0.15 kg, were housed in individual metabolic cages. The treatments included five levels of yeast combination 0, 0.15, 0.3, 0.45, and 0.6% of the DM offered in kg animal-1 day-1 blended into a diet with a 20:80 ratio of corn silage to concentrate based on DM. Employing a 5x5 Latin square design, the study involved five animals over five periods, thus creating 25 experimental units. Regression analysis conducted at a significance level of 5% indicated no effects of the treatments on consumption variables; however, there was a significant lack of model fit (LMF), with the average DM consumption being 1343.0 g animal-1 day-1. The treatments also showed no effect on the apparent digestibility variables, which averaged 86.9% for DM. Similarly, the nitrogen balance variables were unaffected by the yeast levels, as indicated by the LMF effect showing that the data did not fit the regression model; the average retained nitrogen was 45.3 g animal-1 day-1. Energy measurements, including gross energy (GE) ingested, digestible energy (DE), metabolizable energy (ME), and metabolizability, did not fit the regression model, with averages of 5549, 2685, 2504 kcal animal-1 day-1, and 42.6%, respectively. Neither fecal nor urinary GE excretion was influenced by the treatments. In conclusion, the combination of active and inactive yeast does not alter the intake, nutrient digestibility, nitrogen, or energy balance of lambs fed a high-concentrate diet.
Combinação de levedura ativa com inativa e seu uso como aditivo para borregas confinadas: parâmetros nutricionais
Keywords: Prebiotic; Probiotic; Saccharomyces cerevisiae; Sheep; Starch